6-(7-nitro-2, 1, 3-benzoxadiazol-4-ylthio) hexanol: a promising new anticancer compound. Issue 1 (13th February 2018) - Sha, Huan-huan; Wang, Zhen; Dong, Shu-chen; Hu, Tian-mu; Liu, Si-wen; Zhang, Jun-ying; Wu, Yang; Ma, Rong; Wu, Jian-zhong; Chen, Dan; Feng, Ji-feng
Abstract : The 7-nitro-2, 1, 3-nitrobenzoxadiazole (NBD) derivatives are a series of compounds containing the NBD scaffold that are not glutathione (GSH) peptidomimetics, and result in a strong inhibition of glutathione S-transferases (GSTs). Growing evidences highlight their pivotal roles and outstanding anticancer activity in different tumor models. In particular, 6-(7-nitro-2, 1, 3-benzoxadiazol-4-ylthio) hexanol (NBDHEX) is extensively studied, which is a very efficient inhibitor of GSTP1-1. It triggers apoptosis in several tumor cell lines and this cytotoxic activity is observed at micro and submicromolar concentrations. Importantly, studies have shown that NBDHEX acts as an anticancer drug by inhibiting GSTs catalytic activity, avoiding inconvenience of the inhibitor extrusion from the cell by specific pumps and disrupting the interaction between the GSTP1-1 and key signaling effectors. Additionally, some researchers also have discovered that NBDHEX can act as late-phase autophagy inhibitor, which opens new opportunities to fully exploit its therapeutic potential. In this review, we summarize the advantages, anticancer mechanisms, and analogs of this compound, which will establish the basis on the usage of NBDHEX in clinical applications in future.